Primaryb realignment of Traumatic posterior urethral rupture. - Hussein, Malath A. (AL-Kindy College Medical Journal, 2011)
Background: Posterior urethral rupture remainsone of the most difficult and controversial injuriesto treat and its management still controversial.Aim: To assess the effect of primaryrealignment of posterior urethral rupture.Methods: in this study, 20 patients (mean age24.7 years, range 12 to 39 years) were admitted toal-kindey teaching hospital, Baghdad, Iraq, withcomplete posterior urethral rupture associated withfractured pelvis following trauma (3 cases of fallfrom high, 17 cases of road traffic accidents). Allthe patients were operated upon at the day ofaccident to establish the alignment of the posteriorurethra on a Foley's catheter with bladder drainageby suprapubic catheter. Patients were evaluatedpost-operatively for urinary incontinence, erectiledysfunction, and urethral stricture. They werefollowed up for a mean period of 17 months(range, 10 to 20 months).Results: posterior urethral rupture wasassociated with pelvic fractures in 18 of 20patients (90%), and only one case had bladderrupture (5%). Seven patients (35%) had evidenceof post operative stricture. Erectile dysfunctionwas reported by 2 patients (10%). none of thepatients had urinary incontinence.Conclusion: Primary realignment of PUR is asimple procedure associated with low morbidity. Itis recommended for patients who are stable andhave no other significant intra-abdominal andpelvic organ injuries.